Assessment Wind Energy in the Cental Region of Thailand - Tunphibal, Kanchanaporn; Taweekun, Juntakarn (International Journal of Integrated Engineering, 2024)
This study assesses the potential of wind energy resources in central Thailand using data from seven wind measurement stations (Ayutthaya, Bang Na, Chai Nat, Kampaeng Saen, Lop Buri, Nakorn Sawan, and Pathum Thani) and two wind turbine models, namely AN Bonus 1300/62 and Vestas Wind System A/S. The analysis is conducted using the Wind Atlas Analysis and Application Program (WAsP) to examine wind speed data collected over a three-year period at the seven stations. The objective is to identify the top three areas with the highest Annual Energy Production (AEP). Additionally, the study includes an economic analysis, employing metrics such as Present Value of Cost (PVC), Benefit Cost ratio (BCR), Payback Period (PBP), and Levelized Cost of Electricity (LCOE). The results indicate that the AN Bonus 1300/62 model offers greater cost-effectiveness in areas with high wind speeds and relatively high electricity demand. On the other hand, the Vestas V52 model is more suitable for areas with lower wind speeds and lower investment requirements. Based on these findings, the authors recommend prioritizing wind power development in Ayutthaya, Nakorn Sawan, and Lop Buri, using the AN Bonus 1300/62 model, as these areas exhibit high wind speeds and relatively high electricity demand.Overall, this research provides valuable insights for policymakers and investors, enabling them to make well-informed decisions regarding renewable energy investments in Thailand.